Metabolic disparities in caput, corpus, and cauda epididymis of Hu sheep revealed by LC-MS untargeted metabolomics: implications for sperm maturation - Shi, Shujun; Feng, Yulan; Zhu, Lina; Chen, Zhenghan; Li, Qiao; Zhang, Rui; An, Xuejiao; Yue, Yaojing (Frontiers in Veterinary Science, 2025)
The epididymis is a crucial organ for sperm maturation and storage, with metabolic microenvironmental differences across its functional segments (Caput, Corpus, Cauda) being pivotal to this process. However, the underlying metabolic regulatory mechanisms remain incompletely defined. This study systematically characterized region-specific metabolic profiles in the epididymis of Hu sheep and elucidated their functional associations with sperm maturation. Tissues from the caput, corpus, and cauda of the epididymis from eight Hu rams were subjected to untargeted metabolomic analysis using UHPLC-Q-Exactive HF-X. Differential metabolites were screened by combining multivariate statistical analysis (OPLS-DA, VIP >1) and univariate statistical analysis (student t-test, p < 0.05), with key metabolic networks identified through KEGG pathway enrichment. We detected 3,393 metabolites, including 1,844 differentially abundant metabolites: 1,038 between the caput and corpus, 1,243 between the cauda and caput, and 1,159 between the cauda and corpus. KEGG analysis revealed significant enrichment in biosynthesis pathways, cAMP signaling, and protein digestion/absorption. Our findings demonstrate that compartmentalized metabolic reprogramming—particularly involving choline and L-carnitine—drives sperm maturation, providing critical targets for optimizing semen cryopreservation technologies in Hu sheep.